The Interview Times : Nurdil Nuru | Buraxılış No.8 | Fevral, 2023 ﻿ - El Presidente; Şahməmmədli, Cavid; Kamanga, Nathan; Namazova, Fidan; Eyvazova, Fəridə; Duran, Alejandra Garcia; Ağalarzadə, Mahirə; Nəbiyeva, Jalə; Qədimova, Ayan; Rəhimova, Aliyə (ADA University, 2023)
Nurdil Nuru is currently working as a Technical Architect at IBM in the United States of America. Before IBM, he worked as a "Solution Specialist" and "Salesforce Developer" at Deloitte and Nubessom Consulting. He has his bachelor's degree in computer engineering at ADA University. He is the first person with US citizenship who has served in the Armed Forces of Azerbaijan. He is currently engaged and lives in Texas, USA.

In order to read full interview, click View/Open section below.
Keywords: ADA University--Newspaper.